PENGARUH LOAN TO DEPOSIT RATIO, CAPITAL ADEQUACY RATIO DAN NON PERFORMING LOAN TERHADAP PROFITABILITAS PADA PT. BANK DKI PERIODE 2009-2023 - Rahman Hakim, Ariyasa; Syatoto, Iman (Journal of Research and Publication Innovation, 2024)
This study aims to determine how much LDR, CAR, and NPL affect profitability proxied by Return on asset, this type of research uses secondary data and methods used quantitative descriptive methods and statistical analysis. Popoluasi data used in this study is the Financial Report (Annual Report) of PT. BANK DKI period 2009-2023. While the sample used in this study is the statement of financial position and income statement. For the classical assumption test itself consists of normality Test, multicollinearity Test, Heterochedasticity Test and autocorrelation Test. The data management used in this study is SPSS version 21. Based on the results of T test LDR (X1) of 0,034 > 0,05 which means partially significant effect on profitability (Y), and NPL (X3) of 0,034 > 0,05 which means partially significant effect on profitability (Y), while CAR (X2) of 0,063 > 0,05 which means partially no significant effect on profitability (Y) and F test results obtained from the value of F count 4,720 > F table of 4,46 0,024 > 0,05 which means that there is an effect of LDR, car, and NPL simultaneously on profitability (Roa), coefficient of determination showed that LDR (X1), CAR (X2) and NPL (X3) had a strong effect on ROA by 56% while the remaining 44% were influenced by other factors that were not studied in this study.